METAPHOR TRANSLATION TECHNIQUES IN THE SONG LYRICS IN THE ALBUM ENTITLED DON MOEN OPEN WORSHIP - Azaziah John Silaban; Dwi Aji Prajoko (Universitas Katolik Widya Mandala Surabaya, 2025)
This research was to 1) To describe the types of metaphors in the song lyrics in the album entitled “Don Moen Open Worship”, 2) To analyze techniques used in the English-Indonesian metaphor translation of the song lyrics in the “Don Moen Open Worship album”. The data collection technique of this descriptive qualitative research was document analysis. The data analysis technique was ethnographic (Spradley, 2007), which was conducted by differentiating the data and non-data, taxonomizing them, analyzing their components, and analyzing their cultural themes. The results showed that all types of metaphors were found in the song lyrics, namely structural, orientational, and ontological. The most dominant type was structural because there were many metaphors whose meaning structures of the source domain were richer than the target domain. There were also various translation techniques of metaphor translation, namely established equivalent, explicitation, deletion, reduction, generalization, discursive creation, paraphrase, modulation, particularization, addition, implicitation, transposition, discursive creation + explicitation, and addition + particularization. The dominant type of metaphor translation technique was established equivalent. This was because most of the equivalents of metaphor translation were found in dictionaries and language use.